Development of a Learning Video for the Pias 6 Skirt Pattern for Grade X Students of the Fashion Design Skills Program at MAN 3 Tulungagung - Ayu, Wa Ode Nika; Yuniati, Mita; Marniati, Marniati (Universitas Syiah Kuala, 2025)
This study aims to determine the level of feasibility and effectiveness of video media for learning the 6-pias skirt pattern as a learning medium in the Fashion Design Skills Program for Class X. This study uses the Research and Development (RD) method with the ADDIE development model which includes five stages,namely Analysis, Design, Development, Implementation, and Evaluation. The validators of this study consisted of three media experts and three material experts who were competent in their fields and the trial was conducted on twenty-seven students. The data collection method used the observation method. The research instrument used a questionnaire sheet. The data analysis used was quantitative descriptive analysis. The results of this study indicate that the results of the validation of the material experts obtainedThe average value is 4.50 with a percentage of 90%, and media experts obtained an average value of 4.13 with a percentage of 88.6%, so that the overall average feasibility result is 4.31 with a percentage of 88.2% which is included in the